Farmer management of production risk on degraded lands: the role of wheat genetic diversity in Tigray Region, Ethiopia - di Falco, Salvatore; Chavas, Jean-Paul; Smale, Melinda (International Food Policy Research Institute, 2006)
This paper investigates the effects of wheat genetic diversity and land degradation on risk and agricultural productivity in less favored production environments of a developing agricultural economy. Drawing production data from household survey conducted in the highlands of Ethiopia, we estimate a stochastic production function to evaluate the effects of variety richness, land degradation, and their interaction on the mean and the variance of wheat yield. Ethiopia is a centre of diversity for durum wheat and farmers manage complex variety mixtures on multiple plots. Econometric evidence shows that variety richness increases farm productivity. Variety richness also reduces yield variability but only for high levels of genetic diversity. Simulations with estimated parameters illustrate how planting more diverse durum wheat varieties on multiple plots contributes to improving farmer's welfare.